Blockchain Applications in the Smart Era - Misra, Sanjay; Kumar Tyagi, Amit.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book covers a variety of topics and trends related to blockchain technology for smart era applications. The applications span industries such as transportation, manufacturing, agriculture, finance, retail, logistics, information systems, all far beyond blockchain's original use in cyptocurrency. The authors present variants, new models, practical solutions, and technological advances related to blockchain in these fields and more. The applications within these fields include blockchain and cyber-security, IoT security and privacy using blockchain, security using blockchain for robots, and blockchain in industries 4.0 and society 5.0. A variety of case studies are also included. The book is applicable to researchers, professionals, students, and professors in a variety of fields in communications engineering. Presents challenges and trends in blockchain for applications in manufacturing, health, security, and government finance; Discusses the impact of blockchain on society and industry; Applicable to researchers, professionals, students, and professors in a variety of fields in communications engineering. .
Perspectives of Blockchain in Digital Health in Brazil? -- Edge Information Systems Based Blockchain Frameworks for Industrial IoT: A Novel Approach -- A Secure Electronic Voting System Using Multifactor Authentication and Blockchain Technologies -- Enhanced Security and Privacy Issue in Multi-tenant environment of Green Computing using Blockchain Technology -- Application of Crypto-Blockchain Technology for Securing Electronic Voting Systems -- Enhanced Hash Values and Public Keys Infrastructure Generations for Blockchains using Sooner Lightweight Cryptography -- A Prediction Model for Bitcoin Cryptocurrency Prices -- Blockchain-Based Framework for Secure Medical Information in Internet of Things System -- Blockchain Technology and Organizational Practices: The Case of Nigerian Academic Libraries -- A Comparative Study of Regression Analysis for Modelling and Prediction of Bitcoin Prices -- Adoption of Blockchain technology in the Indian business market:Obstacles and opportunities -- Machine Learning, IoT and Blockchain Integration for Improving Process Management Application Security -- A Blockchain-Powered Energy Monitoring System -- Multifactor IoT Authentication System for Smart Homes using Visual Cryptography, Digital Memory and Blockchain Technologies.
Keywords: Telecommunication; Cooperating objects (Computer systems).; Computational intelligence; Big data; Cryptography; Data encryption (Computer science).; Communications Engineering, Networks; Cyber-Physical Systems; Computational Intelligence; Big Data; Cryptology; Blockchains (Databases); Artificial intelligence